Downregulation of miR-221 Inhibits Cell Migration and Invasion through Targeting Methyl-CpG Binding Domain Protein 2 in Human Oral Squamous Cell Carcinoma Cells. (16th December 2015) - He, Shuqi; Lai, Renfa; Chen, Dan; Yan, Wangxiang; Zhang, Zhaoqiang; Liu, Zhiguo; Ding, Xueqiang; Chen, Yu
Abstract : Oral squamous cell carcinoma (OSCC), the most frequent of all oral cancers, is a type of highly malignant tumors with a high capacity to invade locally and form distant metastases. An increasing number of studies have shown that microRNAs (miRNAs) play an important role in regulating cancer metastasis and invasion. In the present study, we detected the expression of miR-221 in two highly metastatic OSCC cell lines and two OSCC cell lines that are less metastatic using quantitative real-time PCR analysis (qRT-PCR). The qRT-PCR results indicate that miR-221 is upregulated in highly metastatic OSCC cell lines. Then, miR-221 expression was knocked down by transfection with miR-221 inhibitor, and UM1 cell migration and invasion were assessed using transwell migration and invasion assays. The results indicate that inhibition of miR-221 suppressed migration and invasion of UM1 cells. Furthermore, methyl-CpG binding domain protein 2 (MBD2) was identified as a direct target gene of miR-221. Additionally, MBD2 silencing could partly reverse the effect of miR-221 on cell migration and invasion. In conclusion, downregulation of miR-221 inhibits cell migration and invasion at least partially through targeting MBD2 in the human OSCC cell line UM1.